2018
DOI: 10.2196/jmir.9923
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Direct Impact of a Gamified Versus Nongamified Well-Being Intervention: An Exploratory Experiment

Abstract: BackgroundGamification is a promising strategy to increase the effectiveness of Web-based mental health interventions by enhancing engagement. However, because most studies focus on the longer term effects of gamification (eg, effectiveness or adherence at the end of the intervention period), there is limited insight into how gamification may enhance engagement. Research implies that gamification has a direct impact at the time of use of the intervention, which changes the experience of the users, and thereby … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 50 publications
1
61
0
4
Order By: Relevance
“…Importantly, the attrition rate in the group using a gamified mental well-being app was significantly reduced, supporting the idea that gamification may indeed strengthen adherence when using mental health apps. This is in line with a study by Kelders et al [36], who investigated the impact of a gamified versus a non-gamified web-based well-being intervention. According to the authors, gamification increased involvement and flow when using the intervention.…”
Section: Plos Onesupporting
confidence: 91%
See 3 more Smart Citations
“…Importantly, the attrition rate in the group using a gamified mental well-being app was significantly reduced, supporting the idea that gamification may indeed strengthen adherence when using mental health apps. This is in line with a study by Kelders et al [36], who investigated the impact of a gamified versus a non-gamified web-based well-being intervention. According to the authors, gamification increased involvement and flow when using the intervention.…”
Section: Plos Onesupporting
confidence: 91%
“…According to the authors, gamification increased involvement and flow when using the intervention. Although we did not test this directly, based on the results by Kelders et al [36], it is also reasonable to suggest that higher involvement and flow led to a reduced attrition rate in the gamified app group in our study. Importantly, however, that Kelders et al found that gamification did not increase behavioral engagement in terms of time spent with the intervention or exercises completed [36].…”
Section: Plos Onementioning
confidence: 61%
See 2 more Smart Citations
“…Also, 106 respondents gave a "neutral" answer while 28 respondents gave "disagree" answer and the remaining 22 respondents gave very "disagree" answers on this topic. Recent studies show that the use of badges is low in terms of treatment (Kelders, Spijkerman & Goldberg, 2018 Table 3 visualizes the highest mean of min is 4.06 representing item number seven. 152 respondents responded "strongly agree" and 144 respondents responded in agreement.…”
Section: Demography Respondentsmentioning
confidence: 99%